Radiographic bone loss in a Scottish non‐smoking type 1 diabetes mellitus population: A bitewing radiographic study. Issue 9 (14th August 2018) - Plessas, Anastasios; Robertson, Douglas P.; Hodge, Penny J.
Abstract: Background: The dental complications of uncontrolled diabetes include reduced salivary flow rate, candidiasis and periodontal manifestations. A recent meta‐analysis concluded that diabetes patients have a significantly higher severity, but not extent, of destructive periodontal disease than non‐diabetics. The authors reported that most type‐1 diabetes studies using dental radiographic data have not controlled for confounding factors such as smoking. The aim of this cross‐sectional study was to compare radiographic alveolar bone loss between type 1 diabetes (T1DM) and non‐diabetes (NDM) participants in a Scottish non‐smoking population. Methods: Digital bitewing radiographs for 174 Scottish adults never or ex‐smoker (>5 years) participants (108 T1DM, 66 NDS), recruited from outpatient clinics throughout Greater Glasgow and Clyde, were included in the analysis. A single blinded, trained, and calibrated examiner recorded the radiographic bone loss seen on bitewing radiographs using the digital screen caliper (Screen Calliper ICONICO version 4.0 (Copyright (C) 2001–6 Iconico), New York). The bone loss was measured as the distance between the cemento‐enamel junction (CEJ) and the deepest radiographic alveolar bone margin interproximally of each tooth. Results: T1DM participants had more radiographic alveolar bone loss throughout the all teeth measured (median:1.27 mm versus 1.06 mm, P < 0.001) and more than a two‐fold increase in the risk of having sites with ≥2 mm periodontal destruction (OR = 2.297, 95%CI 1.058 to 4.986, P = 0.036) compared with non‐diabetes subjects. Conclusions: Patients suffering from type 1 diabetes are at higher risk of periodontitis even when controlling for multiple possible confounding factors and this difference can be detected on routine dental radiographs at an early stage. These data confirm radiographically the previously reported association between T1DM and periodontal bone loss.